International Second Home Retirement Motives in Malaysia: Comparing British and Japanese Retirees - Wong, K.M.; Musa, G. (Taylor & Francis, 2015)
Generally, the international second home (ISH) retirement develops from the need for better life quality of the aging population globally. “Malaysia My Second Home” (MM2H) is an ISH scheme that aims to attract inbound retiree market in Malaysia. This study explores the retirement motivations and their influences on ISH decision using the combination of push–pull travel motivation theory and tri-reference point (TRP) theory, while simultaneously comparing the British and the Japanese retirees. We interviewed 26 MM2H participants in depth and content analyzed the data with qualitative NVivo software. Other than common motivations shared by both groups, there are also distinct differences, especially with regards to environmental preference and risk taking. Only two motives fit into all the three elements of TRP, with most motives either explained by a single or dual reference point. Based on the findings, the study proposes its knowledge, marketing, and managerial implications.